2017
DOI: 10.1159/000485905
|View full text |Cite
|
Sign up to set email alerts
|

Potential Involvement of MiR-30e-3p in Myocardial Injury Induced by Coronary Microembolization via Autophagy Activation

Abstract: Background/Aims: Coronary microembolization (CME) can lead to no-reflow or slow reflow, which is one of the important reasons for loss of clinical benefit from myocardial reperfusion therapy. MicroRNAs and autophagy are heavily implicated in the occurrence and development of almost all cardiovascular diseases. Therefore, the present study was designed to investigate the role of miR-30e-3p and autophagy in CME-induced myocardial injury rat model. Methods: Sixty rats were randomly divided into six groups: sham, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 36 publications
3
21
0
Order By: Relevance
“…Downregulation of miR-30e-3p was previously observed in coronary microembolization and was associated with myocardial injury mediated by impairment of autophagy in cardiomyocytes [86]. Therefore, the downregulation of miR-30e-3p found in this study may be involved in vascular dysfunction related to the thrombosis in CVD.…”
Section: Discussionsupporting
confidence: 66%
“…Downregulation of miR-30e-3p was previously observed in coronary microembolization and was associated with myocardial injury mediated by impairment of autophagy in cardiomyocytes [86]. Therefore, the downregulation of miR-30e-3p found in this study may be involved in vascular dysfunction related to the thrombosis in CVD.…”
Section: Discussionsupporting
confidence: 66%
“…Some of the miRNAs targeting the COVID-19 genome showed low abundance (down-regulated) with some underlying conditions ( Table 7). For example, miR-15b-5p (Coronary artery disease) [37], miR-15a-5p (Kidney disease) [38], miR-520c-3p (obesity/diabetes) [39], miR-30e-3p (Myocardial Injury) [40], miR-23c (hepatocellular carcinoma) [41], miR-30d-5p (non-small cell lung cancer) [42], miR-4684-3p (colorectal cancer) 43], and miR-518a-5p (Gastrointestinal stromal tumors) [44] down-regulated in pathophysiological condition.…”
Section: And Supplementarymentioning
confidence: 99%
“…Importantly, 17 of these miRNAs were the same as those that were increased in ZL-Rap (Table 1). Among these miRNAs, miR-30e-3p is shown to be suppressed by insulin [45]; however, another study showed that its suppression is associated with myocardial injury induced by coronary microembolization via autophagy activation [46]. Moreover, miR-92b-3p is shown to be suppressed by hypoxia [47], but its expression is elevated in the heart tissues of both Rap-treated groups.…”
Section: Resultsmentioning
confidence: 99%